Evaluasi Efektivitas Penggunaan Dana Bantuan Operasional Sekolah (BOS) di SMA Swasta Kristen Harapan Denpasar pada Masa Pandemi Covid-19 - Citariani, I Gusti Ayu Oka; Ariawan, I Putu Wisna; Werang, Basilius Redan (Pascasarjana Universitas Pendidikan Ganesha, 2023)
This study aims to find out the results of evaluations separately and together on context, input, process, product and the constraints that occur in implementing the use of BOS funds at Harapan Christian Private High School Denpasar, during the COVID-19 pandemic. This research is a program evaluation research using the CIPP model. The population in this study were all residents of Harapan Christian Private High School Denpasar. Determination of the sample in this study using a purposive sampling technique, with a total sample of 39 people consisting of school principals, deputy principals, school treasurers, BOS treasurers, administration, teachers. Context, input, process and product data in this study were collected by questionnaire using a Likert scale of 1-5. The data analysis method used in this study is a quantitative descriptive analysis method. To determine the effectiveness of the implementation of the use of BOS funds, raw scores were transformed into Z scores and then into T-Scores and then verified into the Glickman Quadrant. Based on the research that has been done, the results show that: 1) the implementation of the use of BOS funds in terms of the context component is classified as ineffective, 2) the implementation of the use of BOS funds in terms of the input component is classified as ineffective, 3) the implementation of the use of BOS funds in terms of the process component classified as effective, 4) implementing the use of BOS funds in terms of product components classified as ineffective, 5) evaluation results on the implementation of the use of BOS funds in terms of the context, input, process and product components, the results are less effective (–+-).